Dagupan (CAMADA) final report Alatec-Harris-Tym Consulting Group and Angel Lazaro & Associates. - Philippines. National Economic and Development Authority ([Pasig] National Economic and Development Authority, 1994)
On title: Baguio and Dagupan Urban Planning Project.
Contents : Vol. a. Hazards--v.b. Planning Studies v. c--Socio-economic aspects --v.d Technical studies--v.e Implementation and Finance.
Keywords: City planning -- Philippines -- Dagupan; Economic development projects -- Philippines -- Dagupan